View of Bethania, 1880. - Unknown (Forsyth County Public Library, 1880)
Oversize.
View of Bethania, 1880. Bethania Moravian Church and steeple can be seen in the background. A plank footbridge over Muddy Creek can be seen in the foreground.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth; Bethania (N.C.)